Prognosis of nasopharyngeal carcinoma with insufficient radical dose to the primary site in the intensity‐modulated radiotherapy era. Issue 10 (16th July 2019) - Lu, Tianzhu; Xie, Xingyun; Guo, Qiaojuan; Zhan, Shenghua; Lin, Cheng; Lin, Shaojun; Zhang, Yu; Zong, Jingfeng; Pan, Jianji
Abstract: Background: It was reported that reduced radiotherapy is feasible for children with nasopharyngeal carcinoma (NPC) and papilloma virus‐positive oropharyngeal cancer. Therefore, we performed this study to explore the prognosis of reduced‐dose radiation in adult with NPC. Methods: Between 2004 and 2013, we retrospectively analyzed 19 patients histologically diagnosed with NPC, who received <66 Gy radiation therapy. Ten patients receiving <54 Gy to the primary site were group A. Nine patients receiving ≥54 Gy were group B. Results: Thirteen patients received induction chemotherapy (IC) for two or three cycles. In group A, the 5‐year overall survival (OS) was 50.0%. For group B, the 5‐year OS, locoregional relapse‐free survival, progression‐free survival, and distant metastasis‐free survival were 88.9%, 100.0%, 88.9%, and 88.9%. Group B had a better prognosis than group A on OS (88.9% vs 50.0%, P = .03). Conclusion: Patients receiving ≥54 Gy but <66 Gy with IC achieved good local control and long‐term survival.